Impact of Sarcopenia on Two-Year Mortality in Patients with HCV-Associated Hepatocellular Carcinoma After Radiofrequency Ablation - Salman A; Salman M; Moustafa A; Shaaban HE; El-Mikkawy A; Labib S; Youssef A; Omar MG; Matter M; Elkassar H (Journal of Hepatocellular Carcinoma, 2021)
Ahmed Salman,1 Mohamed Salman,2 Ahmed Moustafa,3 Hossam El-Din Shaaban,4 Ahmed El-Mikkawy,5 Safa Labib,1 Ahmed Youssef,1 Mahmoud Gouda Omar,1 Mohamed Matter,6 Hesham Elkassar1 1Internal Medicine Department, Faculty of Medicine, Cairo University, Cairo, Egypt; 2General Surgery Department, Faculty of Medicine, Cairo University, Cairo, Egypt; 3Department of Endemic Medicine and Hepatology, Faculty of Medicine, Cairo University, Cairo, Egypt; 4Gastroenterology Department, National Hepatology and Tropical Medicine Research Institute, Cairo, Egypt; 5Hepatology and Gastroenterology Department, Theodor Bilharz Research Institute, Cairo, Egypt; 6Radiodiagnosis Department, Faculty of Medicine, Alazhar University, Cairo, EgyptCorrespondence: Ahmed SalmanInternal Medicine Department, Faculty of Medicine, Cairo University, 110 L Hadayek Alahram, 11311, Cairo, EgyptTel +201000468664Email awea844@gmail.comPurpose: Radiofrequency ablation (RFA) appears effective for the treatment of hepatocellular carcinoma (HCC). Evaluation of prognostic factors is imperative for patient selection and improving treatment efficacy. This study aimed to assess sarcopenia as a predictor of the outcome of RFA in patients with HCC.Methods: This prospective study included all patients with HCC on top of HCV-related cirrhosis who underwent RFA and followed up for a minimum of two years. CT scan was used to determine the skeletal muscle index at the psoas, erector spinae, quadratus lumborum, transversus abdominis, external and internal obliques, and rectus abdominis muscles. Cross-sectional areas were calculated to obtain a lumbar skeletal muscle index (L3-SMI).Results: A total of 97 patients were enrolled in the study. The L3-SMI was 46.2± 12.1 cm2/m2. Older age was the only risk factor associated with sarcopenia (p = 0.001). The overall survival at two years for the whole group was 65.2%. Sarcopenia and MELD score were independent predictors of OS at two years with HR of 7.6 (95% CI: 3.1– 18.7) and 2.2 (95% CI: 1.0– 4.8), respectively. Recurrence-free survival was 84.1% at two years. Recurrence was not affected by all factors, including sarcopenia.Conclusion: Sarcopenia is a surrogate predictor of overall survival at two years in HCC patients after RFA. Sarcopenia assessment might be an additional prognostic indicator with conventional biomarkers to optimize the selection criteria for receiving RFA for early-stage HCC.Keywords: sarcopenia, mortality, hepatocellular carcinoma, radiofrequency ablation